UI/UX DESIGN OF INSTITUTIONAL REPOSITORY APPLICATIONS USING USER CENTERED DESIGN (UCD) METHOD - Saputra, Dwi Fajar; Edyana, Fajar (Jurnal Sistem Informasi Bisnis (JUNSIBI), 2023)
The Library Service has become an essential tool in enabling the public to participate in monitoring and improving university services. The Library in central Java currently has a limited forum to accommodate information related to institutional repository services. The impact of no information system is that institutional repositories made by the community are not promoted or even seen by the community or stakeholders in the Library area. This research aims to create a web-based public institutional repository service application design in the Library. The results of this research are to produce an application design to accommodate all institutional repository information made by the service in the Library and make it easier for the user to receive information so that it can disseminate institutional repository.